This research was to study in vitro callus induction and somatic embryogenesis in oil palm from leaf explants. Young leaf segments from mature oil palm were cultured on MS medium supplemented with different concentrations of 2,4-D with or without addition of 2 g/l activated charcoal (AC) or 2,4-D and picloram. Embryogenesis induction was done using MS medium containing 2,4-D 450 mM and benziladenine 4.4 mM with 3g/l activated charcoal. The treatment of 2,4-D 15 mM resulted in the highest percent - . YUSNITA; DWI HAPSORO (Bogor Agricultural University, Indonesia, 2011)
This research was to study in vitro callus induction and somatic embryogenesis in oil palm from leaf explants. Young leaf segments from mature oil palm were cultured on MS medium supplemented with different concentrations of 2,4-D with or without addition of 2 g/l activated charcoal (AC) or 2,4-D and picloram. Embryogenesis induction was done using MS medium containing 2,4-D 450 mM and benziladenine 4.4 mM with 3g/l activated charcoal. The treatment of 2,4-D 15 mM resulted in the highest percentage of callus induction. The treatment of 2,4-D and AC showed that 2,4-D 450 mM and AC led to higher percentage of callus induction than that of 2,4-D 400 mM and 2 g/l AC. Embryogenesis occured in 27 out of 250 clumps of primary callus was occurred after 2-3 times subcultures. Somatic embryo development occurred when the embryogenic callus was transferred on the same basal medium supplemented with casein hydrolysate with 1 mM BA or growth regulator free basal medium with 2 g/l activated charcoal.